Removal Of So2 And No From Flue Gas Using Sorbent Derived From Rice Husk Ash - Lau , Lee Chung (2010)

(untitled)
The main objective of this research is to synthesize a sorbent from rice husk for simultaneous removal of SO2 and NO from flue gas. In this study, two types of rice husk ash (RHA), i.e. RHAraw and RHAinc were used. RHA was hydrated with CaO in NaOH solution and subsequently impregnated with CuO. The research was carried out by a statistical investigation on sorbent preparation parameters using Design Expert software. Investigated sorbent preparation parameters were CuO loading, RHA/CaO ratio, hydration period and NaOH concentration. The results showed that CuO loading and NaOH concentration are the major parameters that affect the sorbent’s desulfurization and denitrification activity. The optimum sorbent preparation for RHAraw and RHAinc sorbents were 3.06% CuO loading, RHAraw/CaO ratio of 1.41, 8.05 hours of hydration period, NaOH concentration of 0.80M and 3.04% CuO loading, RHAinc/CaO ratio of 1.41, 19.95 hours of hydration period, NaOH concentration of 0.20M, respectively. In addition, the effect of operating parameters such as temperature, initial SO2 and NO concentration towards RHAraw and RHAinc sorbents’ desulfurization and denitrification activity were also studied. Two types of performances investigated were sorption at which 100% pollutants removal was sustained and equilibrium removal efficiency.